2005
DOI: 10.1007/s00421-004-1307-y
|View full text |Cite
|
Sign up to set email alerts
|

A single session of resistance exercise enhances insulin sensitivity for at least 24 h in healthy men

Abstract: The aim of the present study was to determine whether a single session of resistance exercise improves whole-body insulin sensitivity in healthy men for up to 24 h. Twelve male subjects (23 +/- 1 years) were studied over a period of 4 days during which they consumed a standardized diet, providing 0.16 +/- 0.01 MJ.kg(-1).day(-1) containing 15 +/- 0.1 energy% (En%) protein, 29 +/ -0.1 En% fat and 55 +/- 0.3 En% carbohydrate. Insulin sensitivity was determined 24 h before and 24 h after a single resistance exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 62 publications
(109 reference statements)
4
72
1
3
Order By: Relevance
“…As previously mentioned, skeletal muscle mass is in charge of insulin dependent glucose uptake in the human body. Insulin dependent glucose uptake capacity is directly related to muscle mass and inversely to fat mass (21). Based on our study, blood glucose reduction during training has been strongly and positively associated with muscle mass percentage.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…As previously mentioned, skeletal muscle mass is in charge of insulin dependent glucose uptake in the human body. Insulin dependent glucose uptake capacity is directly related to muscle mass and inversely to fat mass (21). Based on our study, blood glucose reduction during training has been strongly and positively associated with muscle mass percentage.…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, even one session moderate to intense endurance training clearly improves insulin sensitivity or glucose resistance (21). GLUT-4 protein express has an important role in insulin dependent glucose uptake of skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of a single bout of resistance exercise on insulin action is likely to be temporary because insulin sensitivity or glucose tolerance is enhanced 12-24 h after a single bout of resistance exercise in some (22)(23)(24) but not all studies (25). Extrapolation between this and previous studies (22)(23)(24) is difficult because of differences in the type of subjects and methods used to measure insulin sensitivity. In the present study, insulin action was also measured 24 h after the completion of repeated bouts of resistance exercise over a 7-day period.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, resistance training also improves muscle strength, power and functional capacity, which facilitates the adaptation towards a more active lifestyle (Evans 1995;Macaluso and De Vito 2004). Although there is some discrepancy in the existing literature, we (Koopman et al 2005) as well as others (Fenicchia et al 2004;Fluckey et al 1994) have recently shown that even a single resistance exercise session can improve whole-body insulin sensitivity for up to 24 h after cessation of exercise. In line with the acute stimulating effects of endurance exercise on post-exercise insulin sensitivity (Bogardus et al 1983), it has been speculated that the acute effects of resistance exercise on whole-body insulin sensitivity are also attributed to the reduction of the intramyocellular glycogen and/or lipid stores (Koopman et al 2005).…”
Section: Introductionmentioning
confidence: 94%